157k views
18 votes
Solve: (a-7)(a+1) = 0

1 Answer

7 votes

Answer:

a = −1 or a = 7

Explanation:

Let's solve your equation step-by-step.

( a − 7 ) ( a + 1 ) = 0

Step 1: Simplify both sides of the equation.

a^2 − 6a − 7 = 0

Step 2: Factor left side of equation.

( a + 1 ) ( a − 7 ) = 0

Step 3: Set factors equal to 0.

a + 1 = 0 or a − 7 = 0

a = −1 or a = 7

User Sgmorrison
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.